Effect of Capital Structure on Growth of Nigerian Quoted Consumer Goods Firms - SHIYANBOLA, Alice Anese; ALU, Chituru Nkechinyere; AKINSANYA, Rebecca; TIMILEHIN, Ajiboso Abdullah (Archives of Business Research, 2022)
In a bid to responding to market demand, attaining business stability and a decent profit increase, growth has become the quest of all business owners. The study examined capital structure on growth of Nigerian quoted consumer goods firms. The population consisted of 20 Nigerian consumer goods companies as of 31st December 2018 out of which, 10 were selected as the sample size. Descriptive and inferential statistics were used for data analysis. The study revealed capital structure has no significant influence on the revenue growth of Nigerian quoted consumer goods firms (Adj.R2= 0.050510, F(6) = 1.702302, p>0.05); capital structure significantly affects total assets growth of Nigerian quoted consumer goods firms (Adj.R2= 0.073621, F(6) = 3.622586, p<0.05) and there is no significant relationship between capital structure and the earnings growth of Nigerian quoted consumer goods firms (Adj.R2= -0.025329, F(6) = 0.184805, p>0.05). The study found that capital structure has no significant influence on earnings growth and revenue growth but has a significant relationship on total assets growth of Nigerian quoted consumer goods firms. The study recommended that management should increase equity and long-term debts and reduce short-term debts so as to raise firms’ revenue and also have an understanding of the capital structure disclosure and how it affects revenue growth. Regulatory agencies should ensure assets growth disclosure, revenue, and earnings according to the laid down standards in order to enhance growth. This will boost investment in firms and in turn, raise the bar in performance and growth.